ANALISIS PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SURAT KABAR SUARA MERDEKA PADA MASYARAKAT SEMARANG - Setiawan, Donny; Khasanah, Imroatul (Diponegoro Journal of Management, 2016)
This research is motivated their sales decline can be seen from the sales data Suara Merdeka daily newspaper from 2009 to 2013 in the can from the circulation / marketing PT Suara Merdeka Press. As for the issue of research that will be developed is "How to increase the purchasing decisions of consumers against the daily newspaper Suara Merdeka? The purpose of this study was to analyze the effect of price perception, product quality and brand image influence on purchase decisions in the Daily Newspaper Society Suara Merdeka in Semarang.The sample used in the study were 100 respondents. In this study sampling technique uses accidental sampling is sampling conducted by questionnaire to be filled to consumers who are buying repeatedly against the daily newspaper Suara Merdeka. Data were analyzed using factor analysis to test the validity of the question items, Cronbach's Alpha to test the reliability of the instrument, multiple regression analysis, to examine the influence of the independent variables were tested by t-test to test and prove the partial effect of each independent variable.Based on the analysis, regression equation: Y = 0.431 + 0.395 X1 + 0.326 X2 X3. Based on the results of multiple regression analysis, three independent variables were the most in influencing the purchase decision is the perception of price, followed by the quality of the product and brand image. Hypothesis testing using t test showed that three independent variables studied were perceptions price, product quality and brand image positive and significant impact on purchasing decisions. Then through the F test can be seen  that  the  three  independent  variables  is  feasible  to  test  the  dependent  variable purchase decision. Figures adjusted R2 is 0.526, meaning 52.6% of the variation of the purchase decision can be explained by the variation of all three independent variables namely Perception price, product quality and brand image, while the rest (100% - 52.6% = 47.4 %) is explained by other causes outside the model